1987
DOI: 10.1785/gssrl.58.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Activity in the Permian Basin Area of West Texas and Southeastern New Mexico, 1975–79

Abstract: A seismic network of 12 self-contained, radio-telemetered seismograph systems was operated in the Kermit, Texas area for a period of 46 months. The main object of this study was to improve our understanding of the seismicity of this region where the first events were observed in 1964 and the first feit event occurred in 1966. Over 1300 events were located during this study, and the hypocenters displayed complex relationships with known geologie structures and oll field activity. Swarm activity was prominent, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The network recorded more than 2000 earthquakes, of which about 1300 were located. There were several different investigations analyzing these data (Rogers and Malkiel, 1979;Keller et al, 1987;Doser et al, 1992); all found that much of this seismicity occurred within several active oil and gas fields, notably the WarWink, Kermit-Keystone, and Apollo-Hendrick Fields. The investigations all concluded the seismicity was probably induced but that more than one mechanism was responsible.…”
Section: Permian Basin 1966 Present: Probably Inducedmentioning
confidence: 99%
“…The network recorded more than 2000 earthquakes, of which about 1300 were located. There were several different investigations analyzing these data (Rogers and Malkiel, 1979;Keller et al, 1987;Doser et al, 1992); all found that much of this seismicity occurred within several active oil and gas fields, notably the WarWink, Kermit-Keystone, and Apollo-Hendrick Fields. The investigations all concluded the seismicity was probably induced but that more than one mechanism was responsible.…”
Section: Permian Basin 1966 Present: Probably Inducedmentioning
confidence: 99%
“…Among the natural events are the two largest earthquakes in the state (Figure a): the 16 August 1931 Valentine earthquake with moment magnitude M W 6.3 (Doser, ) and the M W 5.7 14 April 1995 Alpine earthquake (Frohlich & Davis, ). However, analysis of data collected from 1976 to 1979 by a 12‐station regional network indicated that many small earthquakes occurring in the Central Basin Platform and Delaware Basin (Figure b) were related to enhanced recovery or petroleum production operations (Doser et al, ; Frohlich et al, ; Keller et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Delaware Basin is the westernmost (and largest) part of the Permian Basin. Fluid injection associated with hydrocarbon development has long been suspected as triggering mechanisms for earthquakes at a number of sites in the Permian Basin since the 1960s (Rogers and Malkiel, 1979;Keller et al, 1981Keller et al, , 1987. The area also has occasional natural seismicity (Doser et al, 1991(Doser et al, , 1992.…”
Section: Introductionmentioning
confidence: 99%